Mapping & Qualifying Consumption Changes in Product Categories during Recessionary Times - Titus, Ray (Indian Journal of Marketing, 2012)
The term 'Recession' seems to be on everyone's mind. Though the layman may not necessarily know how to define 'recession' on technical lines, its effects are apparent to all in terms of job losses, falling production and consumption. Recession also takes its toll on consumer consumption, both in terms of purchase quality and kind. This paper studies the impact of recession driven changes in consumption, keeping in mind two particular product categories.